Pertanggungjawaban Notaris Sebagai Pejabat Umum dalam Tindakan Wanprestasinya yang Merugikan Klien - Achmad Busro; Monika Sitanggang (Notarius, 2023)
AbstractNotary is a general official who is trusted by the State and the Community by delegated the main tasks and obligations in accordance with Lawi Numberi 2 of 2014 concerningi Amendmentsi to Law Numberi 30 of 2004 iconcerning Notary iPosition. Ini carryingi outi his position as a general official who provides services to the community, a notary does not rule out the possibility of doing a defense that can harm the client. This action must be accounted for by the Notary as a General Officer. The method of approach used in this study is normative juridic. Thei purposei of this writingi is to find outi and analyzei the accountability of the notary for its actions that harm the client. The results of this study are punishment for a Notary who made a negligence of the client. This punishment is in the form of criminal sanctions, civil and administrative, where a notary can be sued by clients who feel disadvantaged, and the category of punishment in accordance with the portion of violations. This study also produced a role of a Notary in providing legal services to the public in accordance with the code of ethics Notary.Keywords: notary; default; client.AbstrakNotaris merupakani pejabati umumi yangi dipercayai olehi Negara dan masyarakati dengan dilimpahkan tugas pokok dan kewajiban sesuai dengan UU Nomori 2 Tahuni 2014 tentangi perubahan atasi Undang-Undangi Nomori 30 Tahuni 2004 Tentangi Jabatani Notaris. Dalam menjalankan jabatannya sebagai pejabat umum yang memberikan jasa kepada masyarakat, Notaris tidak menutup kemungkinan melakukan wanprestasi yang dapat merugikan klien. Tindakan ini harus dipertanggungjawabkan oleh Notaris sebagai pejabat umum. Metodei pendekatani yangi digunakan dalami penelitiani ini adalahi yuridisi normatif. Tujuani penulisan ini untuk mengetahuii dan menganalisisi pertanggungjawaban Notaris atas tindakannya yang merugikan klien. Hasil dari penelitian ini adalah penjatuhan hukuman bagi seorang Notaris yang melakukan suatu kelalaian terhadap klien. Hukuman ini berupa sanksi pidana, perdata, dan administrasi, dimana seorang Notaris dapat digugat oleh klien yang merasa dirugikan, serta kategori pemberian hukuman sesuai dengan porsi pelanggarannya. Penelitian ini juga menghasilkan peran dari seorang Notaris dalam memberikan pelayanan jasa hukum kepada masyarakat sesuai dengan kode etik Notaris.Kata kunci: notaris; wanprestasi; klien.